Autonomy and church membership: resolving Rousseau’s dilemma through Zizioulas’s ecclesiology - Chen, S (Brill Academic Publishers, 2024)
This article explores the theological implications of being a church member in a contemporary context that highly values individual autonomy, by engaging with John Zizioulas’s ecclesiological framework. Initially, the article elucidates the notion of the ‘autonomous self’, drawing upon the intellectual contributions and life experiences of Jean-Jacques Rousseau. It posits that Rousseau’s dilemma of losing self or suffering from loneliness represents the challenge faced by those holding this autonomous anthropological assumption. The article subsequently employs John Zizioulas’s constructs of ontological personhood and communion ecclesiology as counterpoints to this quandary. It contends that Zizioulas’s trinitarian-informed theological anthropology offers an ecclesial means to surmount this existential dilemma, arguing that church membership is an act of participating in divine and familial communion.